Perancangan Interior Co-Working Space di Surabaya - Adelia Marcelina; I Gusti Ngurah Ardana; Sherly de Yong (Intra, 2016)
Co-working is one solution to the problem of expensive land and limited work space with the increasing number of independent entrepreneurs and creative freelancers especially in big cities like Surabaya. Therefore, a co-working space interior need to be designed to match the needs of the people in Surabaya. The design is done using the method of design, namely the observation of user’s need, perform surveying, analyzing data to produce programming, create a schematic and mockups of the study, up to the first evaluation to produce the final product (such as layout, floor plans, ceiling, perspective, scale model and others). The expected result of this design is a public facility that is capable to accommodate community needs in Surabaya especially among young professionals, office space that does not require a huge cost to be built, can interact with other people from different backgrounds, and open up new business opportunities.